Perjodohan Adat: Dampak dan Implikasi Hukum UU No. 16 Tahun 2019 Tentang Perkawinan di Indonesia - Indah, Rambu Hada (Fakultas Syariah INSURI Ponorogo, 2022)
Traditional matchmaking in East Sumba Regency has long been considered a tradition that needs to be continued even though it has many weaknesses that need to be avoided. one of them is if matchmaking is closely related to coercion to children who will be matched. The purpose of this study was to see the true meaning of customary matchmaking and the legal impact on perpetrators of forced matchmaking based on Law 16 of 2016 concerning marriage. The research method used in this research is normative empirical based on evidence, both by reviewing legal documents such as laws and by observation and in-depth interviews so that this study can draw clear conclusions regarding the function of matchmaking in the reality of the indigenous people of East Sumba. The results of the study found that on average, customary marriages that had occurred were carried out at the age of 12-16 years. This study 29% of matchmaking that still occurs in East Sumba is carried out by minors, so if this is still the case then the deprivation of independence is certainly an argument that needs to be punished.